Day-to-day Variation in Autonomy-Supportive and Psychologically Controlling Parenting: The Role of Parents' Daily Experiences of Need Satisfaction and Need Frustration. (3rd April 2018) - Mabbe, Elien; Soenens, Bart; Vansteenkiste, Maarten; van der Kaap-Deeder, Jolene; Mouratidis, Athanasios
SYNOPSIS: Objective. Autonomy-supportive and psychologically controlling parenting have been shown to relate to positive and negative developmental outcomes, respectively. Most research that addresses antecedents of these parenting constructs has focused on the predictive role of between-parent differences (e.g., personality). To gain insight in dynamics of within-parent changes in reported parenting, this study focused on daily fluctuations in reported autonomy-supportive and psychologically controlling parenting and examined the role of parents' need satisfaction and need frustration in accounting for those fluctuations. Design. Mothers ( M age = 45) and fathers ( M age = 47) of 198 adolescents ( M age = 15) participated in a 7-day diary study. Results. Multilevel modeling provided evidence for significant day-to-day variability in both parenting dimensions. Daily fluctuations in need satisfaction were related to daily fluctuations in reported autonomy-supportive parenting and daily fluctuations in need frustration were related to daily fluctuations in reported psychologically controlling parenting. These associations were not moderated by between-parent differences in those parenting dimensions. Conclusions. The findings provide evidence for the role of parents' own needs-related experiences in their daily display of autonomy-supportive and psychologically controlling parenting.